Mengembangkan Keterampilan Kemandirian / Menolong Diri Sendiri Pada Anak Usia Dini - Muhammad Al Amin; Roudlotun Nurul Laili; Muhammad Nashir; Ninis Indriani (Lembaga Pengembangan Kinerja Dosen, 2024)
This Community Service aimed to enhance the parents' ability to educate their children to possess self-reliance skills from an early age. The activity considered the importance of self-reliance skills as the foundation for a child's continuous development. A total of 24 parents with early childhood in Rejosari Village, Glagah, Banyuwangi, participated in this program. The method used was education and training conducted interactively, involving active participation from parents and supplemented with direct practice and discussion. The results showed an improvement in parents' knowledge and skills in supporting the development of children's self-reliance skills. Parents became more understanding and skilled in applying self-reliance education methods, as well as identifying and overcoming obstacles that arise in educating their children. This activity also created a learning community among parents, where they could share experiences and strategies for educating children to be more independent. This community service has positively impacted increasing parents' skills and knowledge in supporting the development of self-reliance skills in early childhood.